Report da Intergeo 2018 (GEOmedia, 2018)
INTERGEO 2018 is the international Geo-ICT showcase for data acquisition systems. Topographic tools always more performing, and interest in the laser scanner. As with photogrammetry, positioning accuracy, orientation precision, cloud recording affect data quality. Inertial platforms and GNSS systems will be decisive for surveys with RPAS to ensure accuracy. The VTOLs are affirmed, where the criticality is in the transition in flight.